2015
DOI: 10.1111/clr.12708
|View full text |Cite
|
Sign up to set email alerts
|

Protein biomarkers and microbial profiles in peri‐implantitis

Abstract: The present data suggest that the increased levels of the selected PICF-derived biomarkers of periodontal tissue inflammation, matrix degradation/regulation, and alveolar bone turnover/resorption combined with site-specific microbial profiles may be associated with peri-implantitis and could have potential as predictors of peri-implant diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
124
2
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(135 citation statements)
references
References 50 publications
4
124
2
5
Order By: Relevance
“…Smokers were excluded from the majority of the studies. Two studies included smokers and match the number of smokers in healthy and peri-implantitis groups [20,21]. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Smokers were excluded from the majority of the studies. Two studies included smokers and match the number of smokers in healthy and peri-implantitis groups [20,21]. …”
Section: Resultsmentioning
confidence: 99%
“…Peri-implantitis has been shown to demonstrate a similar pattern of destruction as periodontitis, and MMP upregulation has been associated with irreversible peri-implant connective tissue destruction [28]. Six studies assessed collagenases in PICF in different peri-implantitis lesions which are important around peri-implant tissues, are MMP-1, MMP-3, MMP-8, and MMP-13 and tissue inhibitors [21,29-33]. And according to all included studies, MMPs were reported to be positively correlated with clinical inflammatory conditions around implants [21,29-33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent cross-sectional study [34] where several biomarkers (IL-1β, VEGF, MMP-8, TIMP-2, and OPG) together with periodontopathogenic bacteria (A. actinomycetemcomitans, P. intermedia, P. gingivalis, T. forsythia, and T. denticola) were analysed, MMP-8 did not reveal meaningful difference among groups. Healthy and PI-affected implants were not compared based on the status of natural teeth and no treatment was given, which makes it difficult to compare the result with ours.…”
Section: (A) 3(b)mentioning
confidence: 89%